Persepsi Keluarga dan Masyarakat terhadap Disabilitas dalam Drama Jepang One Liter of Tears: Analisis Konstruksi Sosial Disabilitas melalui Narasi Keluarga Ikeuchi - Lutfi Imanika Vianti (Universitas Palangka Raya, 2026)
Japanese drama One Liter of Tears (2005), adapted from the real diary of Kitou Aya, succeeded in changing how many people in Japan and Asia understand disability. This paper takes a slightly different angle: not from Aya's own experience, but from how her family and people around her viewed, responded to, and adjusted to the presence of disability in their lives. Using the medical and social models of disability, as well as concepts of care and burden, this study analyzes how the drama constructs the disability experience from the perspective of those closest to Aya. The results show that the drama does portray the family's emotional journey from denial, overwhelm, to eventual acceptance. But beneath that, it also unconsciously reinforces stereotypes about the ideal disabled person: obedient, stoic, heroic, and never complaining. Although successful in moving audiences to tears, the representation remains trapped in the medical model paradigm that treats disability as Aya's personal problem, rather than a social issue that needs collective fixing.